LOCAL WISDOM OF THE SOCIETY OF PACITAN REGENCY, EAST JAVA IN PRESERVING THE ENVIRONMENT CONSERVATION - Pambudi, Priyaji Agung (Kementerian Pendidikan dan Kebudayaan, 2021)
Environmental damage caused by exceeding the carrying capacity of the environment was increasingly massive and became the biggest challenge in the 21st century. This study aimed to understand the local wisdom of the society of Pacitan Regency to the environmental conservation. This research applied qualitative approach through physical, social observation, and in-depth interviews, then exploratory descriptive analysis was used to answer the research questions. The people of Pacitan faced severe life pressures due to the dry and arid natural conditions. These pressures encouraged the people various activities that growth and developed into the local wisdom values. There were 14 activities containing the values of local wisdom in managing the environment for the sustainability and fairness of life across generations. The wise environmental management was carried out from generation to generation and passed down through a system of social institutions. The efforts to preserve the local wisdom was used to face the increasingly challenges due to the development era and modernity. The values of local wisdom were firmly held by the community, especially those who live around forest areas. It has become a part of their lives and formed an inseparable socio-ecological system, and forming a pattern of interdependence and mutual benefit. To preserve the local wisdom which played an important role in preserving the environment and encouraged the realization of sustainable development, people participation through non-formal education in daily social interactions was needed.